SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PERGURUAN TINGGI SWASTA SEHAT DENGAN METODE ANALYTICAL HIERARCY PROCESS (AHP) (STUDY KASUS : PROVINSI LAMPUNG) - sulasminarti . (STMIK Dian Cipta Cendikia Kotabumi, 2022)
87.25% of private higher education in Lampung are in clusters 4 and 5. It means that these universities are not included in “healthy” universities. Higher education needs to make changes and improvements. They are both in the direction and goals of higher education related to quality and quantity so that universities are able to compete (Gamar et al: 2016). The problem is how can the government cooperate with the community to monitor and evaluate the health of a university, given a large number of universities in Indonesia, 4,259 PT. To facilitate the supervisory process, a decision support system is needed in determining the quality of higher education, especially private universities. In this case, there are many private universities that have not been included in the category of healthy private universities, therefore a decision support system is needed that is able to answer these problems. In this study, it used the SmartPLS application in processing data from the questionnaire results. From the results of processing using SmartPLS, the weight was able to be used in calculations using the Analytical Hierarchy Process (AHP) method with the Expert Choice application. The results of calculations used the Expert Choice application and it obtained a sequence of criteria that can be used in determining healthy private universities. The sequence of these criteria included the level of concern of higher education on student activities, percentage of doctoral education lecturers, number of study programs that have international accreditation/certification, institutional accreditation, percentage of lecturers in the position of head and professors, accreditation of study programs, service performance. Society, Research Performance, National and International Student Achievement, Ratio of Number of Indexed Publications to Number of Lecturers, Number of Foreign Students, Ratio of Number of Lecturers to Number of Students.